1989
DOI: 10.1002/j.1552-4604.1989.tb03327.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Midazolam Following Intravenous and Oral Administration in Patients with Chronic Liver Disease and in Healthy Subjects

Abstract: To study the effects of cirrhosis of the liver on the pharmacokinetics of midazolam single IV (7.5 mg as base) and p.o. (15.0 mg as base) doses of midazolam were administered to seven patients with cirrhosis of the liver and to seven healthy control subjects. One cirrhotic patient did not receive the oral dose. The distribution of midazolam in both study groups was alike as indicated by similar values of t1/2 alpha, V1 and Vss. Also the plasma protein binding of midazolam was unchanged in the patients with cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 15 publications
5
63
2
2
Order By: Relevance
“…16,17 MacGilchrist et al 16 found a 2-fold decrease in midazolam clearance and a 2.4-fold increase in the elimination half-life, with no change in the volume of distribution in cirrhotic patients after single intravenous doses of 0.075 mg/kg. Pentkiainen et al 17 found similar changes in clearance and half-life in cirrhotic patients receiving 7.5 mg of midazolam intravenously, with no change in the percent unbound in plasma or the volume of distribution. Thus, the most likely effect of cirrhosis on systemic clearance of midazolam results from a decrease in hepatic CYP3A activity.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 MacGilchrist et al 16 found a 2-fold decrease in midazolam clearance and a 2.4-fold increase in the elimination half-life, with no change in the volume of distribution in cirrhotic patients after single intravenous doses of 0.075 mg/kg. Pentkiainen et al 17 found similar changes in clearance and half-life in cirrhotic patients receiving 7.5 mg of midazolam intravenously, with no change in the percent unbound in plasma or the volume of distribution. Thus, the most likely effect of cirrhosis on systemic clearance of midazolam results from a decrease in hepatic CYP3A activity.…”
Section: Discussionmentioning
confidence: 99%
“…This issue seems to be controversial because Thummel et al (1996) observed no sex-related differences in the clearance of midazolam, but Gorski et al (1998) reported women to have a higher oral clearance of midazolam than men. Cirrhosis of the liver reduces the plasma clearance and elimination half-life is prolonged compared with healthy volunteers (Pentikä inen et al, 1989), whereas the volume of distribution remains unchanged.…”
Section: Pharmacokinetics and Biotransformation Of Commonly Used Bmentioning
confidence: 94%
“…MacGilchrist et al (1986) showed that alcoholic cirrhosis was associated with significantly delayed elimination of MDZ and greater sedation after intravenous administration of MDZ. In a later study, Pentikäinen et al (1989) reported that the elimination of MDZ was significantly retarded, but not the hypnotic effects, in patients with cirrhosis. Yang et al (2010) reported that patients with jaundice needed a lower minimum alveolar concentration (MAC) of isoflurane than normal patients to achieve the same depth of anesthesia.…”
Section: Fig 1 Probability Of Unconsciousness Versus the Bis Values mentioning
confidence: 95%
“…Previous studies have shown that both the pharmacokinetics (MacGilchrist et al, 1986;Pentikäinen et al, 1989) and pharmacodynamics (MacGilchrist et al, 1986) of MDZ were significantly impaired in patients with hepatic cirrhosis. The effects of liver function on sensitivity to MDZ and prediction of the BIS for loss of consciousness (LOC) remain unclear.…”
Section: Introductionmentioning
confidence: 99%